A new efficient adaptive control of torsional vibrations induced by switched nonlinear disturbances - Wasilewski, Maciej; Pisarski, Dominik; Konowrocki, Robert; Bajer, Czesław (Zielona Góra: Uniwersytet Zielonogórski)
Torsional vibrations induced in drilling systems are detrimental to the condition of the machine and to the effectiveness of the engineering process. The cause of vibrations is a nonlinear and unknown friction between a drill string and the environment, containing jumps in its characteristics. Nonlinear behaviour of the friction coefficient results in self-excited vibration and causes undesirable stick-slip oscillations. The aim of this paper is to present a novel adaptive technique of controlling vibrating systems.
Keywords: vibration control; adaptive control; linear-quadratic-regulator; drilling control